96 Estimation of palliative care needs of people experiencing homelessness using mortality data and cause-of-death. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Conneely, Aoibheann; Ivers, Jo-Hanna; Barry, Joe; Dunne, Elaine; O'Leary, Norma; Cheallaigh, Cliona Ni
Abstract : Background: People experiencing homelessness have higher standardised mortality rates and higher risk of death than the general population. In recent years, inclusion health services have developed internationally with the aim of addressing extreme health and social inequities. Much of the research exploring delivery of palliative care to people experiencing homelessness is qualitative. We are unaware of a study that has attempted to quantify the palliative care needs of people experiencing homelessness. Aim: To apply cause-of-death based methodology of estimating palliative care needs to deaths of people experiencing homelessness. To evaluate the appropriateness of this methodology to quantify the palliative care needs of this population. Design: Secondary data analysis of a previously reported observational study. Mortality data (2005–2015) of people experiencing homelessness was reviewed for illnesses (malignant and non-malignant) potentially requiring palliative care input, using specific International Classification of Diseases-10 codes. This method, developed by Murtagh et al, has been used widely internationally to calculate both the current and future palliative care needs of populations. Setting and participants: N=361 deaths of people experiencing homelessness in Dublin between 2005–2015. Results: A minimum of 25% of all deaths of people experiencing homelessness would have benefitted from palliative care. This percentage increases according to age-group with at least 64% of people experiencing homelessness over the age of 60 years dying of illnesses which would benefit from palliative care input. Conclusions: Estimating palliative care needs based on single underlying-cause of death has limitations when applying cause-of-death based methodology to a population of people experiencing homelessness. Incorporating multimorbidity would provide a more accurate estimate of need. In developing a palliative care response to inclusion health, older people in homelessness should be considered a priority group.